Influence of microbial community composition and metabolism on air.sea ΔpCO 2 variation off the western Antarctic Peninsula - Moreau, Sébastien (2012)
We studied CO 2 and O 2 dynamics in the western Antarctic Peninsula (WAP) waters in relation to (1) phytoplankton biomass, (2) microbial community primary production and respiration, and (3), for the first time, phytoplankton composition, during summer and fall in 3 consecutive years (2002, 2003 and 2004). The areal average of ΔpCO 2 (the difference between surface seawater and atmospheric partial pressure of CO 2) for the 3 yr was significantly negative (.20.04 ± 44.3 μatm, p < 0.01) during the summer to fall period in the region, possibly indicating a CO 2 sink. In the southern WAP (i.e. south of Anvers Island), ΔpCO 2 was significantly negative (.43.60 ± 39.06 μatm) during fall. In the northern WAP (north of Anvers Island), ΔpCO 2 values showed a more complex distribution during summer and fall (.4.96 ± 37.6 and 21.71 ± 22.39 μatm, respectively). Chlorophyll a (chl a) concentration averaged 1.03 ± 0.25 μg l.1 and was higher in the south of the peninsula. Phytoplankton composition influenced chl a concentration with higher and lower values for diatom-and phytoflagellate-dominated communities, respectively. A significant negative correlation existed between chl a and ΔpCO 2. From incubation experiments performed in the northern WAP, respiration was low (averaging 5.1 mmol O 2 m.3 d.1), and the net community production (NCP) correlated negatively with ΔpCO 2 and positively with %O 2 saturation. However, despite the high NCP values measured, ΔpCO 2 was significantly positive in the northern WAP during the summer to fall period. Strong mixing and lower chl a concentration may explain this result. In contrast, ΔpCO 2 was significantly negative in the southern WAP, possibly because of high surface water chl a concentration.